Willow (Salix spp.) bark hot water extracts inhibit both enveloped and non-enveloped viruses: study on its anti-coronavirus and anti-enterovirus activities - Reshamwala, Dhanik; Shroff, Sailee; Liimatainen, Jaana; Tienaho, Jenni; Laajala, Mira; Kilpeläinen, Petri; Viherä-Aarnio, Anneli; Karonen, Maarit; Jyske, Tuula; Marjomäki, Varpu (Frontiers in Microbiology, 2023)
Introduction: Recurring viral outbreaks have a significant negative impact on society. This creates a need to develop novel strategies to complement the existing antiviral approaches. There is a need for safe and sustainable antiviral solutions derived from nature.Objective:This study aims to investigate the antiviral potential of willow (Salix spp.) bark hot water extracts against coronaviruses and enteroviruses. Willow bark has long been recognized for its medicinal properties and has been used in traditional medicines. However, its potential as a broadspectrum antiviral agent remains relatively unexplored.Methods:Cytopathic effect inhibition assay, virucidal and qPCR based assays were used to evaluate the antiviral potential of the bark extracts. Mechanism of action was investigated using time of addition assay, confocal microscopy, TEM, thermal and binding assays. Extracts were fractionated and screened for their chemical composition using high-resolution LC-MS.Result:The native Salix samples demonstrated their excellent antiviral potential against the nonenveloped enteroviruses even at room temperature and after 45 seconds. They were equally effective against the seasonal and pandemic coronaviruses. Confocal microscopy verified the loss of infection capacity by negligible staining of the newly synthesized capsid or spike proteins. Time-of-addition studies demonstrated that Salix bark extract had a direct effect on the virus particles, but not through cellular targets. Negative stain TEM and thermal assay showed that antiviral action on enteroviruses was based on added stability of the virions. In contrast, Salix bark extract caused visible changes in the coronavirus structure, which was demonstrated by the negative stain TEM. However, the binding to the cells was not affected as verified by qPCR study. Furthermore, coronavirus accumulated in the cellular endosomes and did not proceed ahead after this stage, based on the confocal studies. None of the tested commercial reference samples such as salicin, salicylic acid, picein, and triandrin, had any antiviral activity. Fractionation of the extract and subsequent MS analysis revealed that most of the separated fractions were very effective against enteroviruses and contained several different chemical groups such as hydroxycinnamic acid derivatives, flavonoids and procyanidins. Conclusion:Salix spp. bark extracts contain several virucidal agents that are likely to act synergistically and directly on the viruses.